2022
DOI: 10.34067/kid.0005112022
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnostic Appearance of Thrombospondin Type-1 Domain 7A Autoantibodies in Membranous Nephropathy

Abstract: Background: Pathogenic autoantibodies against thrombospondin type-1 domain 7A (THSD7A) are present in approximately 3% of patients with membranous nephropathy (MN). Compared to PLA2R antibodies, less is known about THSD7A autoantibodies (AB) due to the relative rarity and lack of a commercially, available quantitative immunoassay. Methods: Here we describe the development and validation of a highly quantitative, luciferase immunoprecipitation systems (LIPS) assay for detecting THSD7A AB and used it to study do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Burbelo et al identified the presence of prediagnostic antibodies through screening of a large biorepository of blood samples donated by veterans with the Department of Defense serum repository. 1 The presence of circulating antibodies before transplantation in patients developing early disease recurrence provides further evidence of anti-THSD7A and PLA2R antibodies preceding disease manifestations. [7][8][9] Antibody titers for THSD7A and PLA2R correlate with disease activity, increasing with worsened proteinuria and falling with disease remission.…”
Section: Thsd7a and Pla2r Antibodies As Ideal Biomarkers Of Diseasementioning
confidence: 97%
See 3 more Smart Citations
“…Burbelo et al identified the presence of prediagnostic antibodies through screening of a large biorepository of blood samples donated by veterans with the Department of Defense serum repository. 1 The presence of circulating antibodies before transplantation in patients developing early disease recurrence provides further evidence of anti-THSD7A and PLA2R antibodies preceding disease manifestations. [7][8][9] Antibody titers for THSD7A and PLA2R correlate with disease activity, increasing with worsened proteinuria and falling with disease remission.…”
Section: Thsd7a and Pla2r Antibodies As Ideal Biomarkers Of Diseasementioning
confidence: 97%
“…As such, the entire extracellular domain of THSD7A was used as a source of antigen with adequate expression and high sensitivity for antibody detection. 1 LIPS technology has been used for detection of antibodies of multiple autoimmune and infectious diseases S9-12 . It also provides the capability for multiplexing for testing panels of autoantibodies, such as antinuclear antibodies specificities S13 .…”
Section: Challenges In Autoantibody Detection May Require Use Of Nove...mentioning
confidence: 99%
See 2 more Smart Citations
“…In primary MN, circulating autoantibodies traverse the GBM and bind endogenous podocyte antigens, resulting in subepithelial deposits. However, patients may have circulating antibodies for years prior to clinical presentation [73,74 ▪▪ ]. The dynamics underlying the sudden loss of immune tolerance is unclear but may be informed by factors such as titers of anti-PLA2R antibodies, the ability of antibodies to reach the subepithelial space, the PLA2R epitope specificity, and the ability to activate complement.…”
Section: Pathophysiology Of Autoimmune Dysregulation In Membranous Ne...mentioning
confidence: 99%